Nihilism and the Problem of Future: Biodiversity Destruction As One of the Great Dangers of Technology? - Oliveira, Jelson (ETHICS IN PROGRESS, 2017)
Starting from the example of the Amazon, in Brazil, we intend to analyse how technology (mainly in its biotechnological face) appears as a threat to biodiversity, insofar as it acts through a reduction and standardization: technology needs to reduce diversity to something knowable to be able to control and exploit, in view of human necessities. In this sense, according to Hans Jonas, it is necessary to ask about the horizon of the future giving preference to the negative prognosis (fear rather than hope) to avoid that the harmful consequences of nihilism (marked by the absence of criteria capable of guiding technological action) affect life decisively. In this case, the Enhancement project proposed by transhumanism appears as yet another chapter in the history of risks represented by modern technology.